Value of CEO succession policy on CEO transition - Sivapregasam, Shubasini; Selamat, Aslam Izah; Abdul Rahim, Norhuda; Muhammad, Junaina (Universiti Kebangsaan Malaysia and the Malaysian Accountancy Research and Education Foundation (MAREF), 2019)
Chief Executive Officer (CEO) transition is a continuous process of change in leadership involving removal of existing CEO and replacement of new CEO. Ideally, CEO transition occurs based upon the CEO Succession Policy developed by the Board of Directors. The CEO succession plan and policy is important because it reduces the impact of a CEO's sudden removal on the firm. In recent time, there is an immense increase in CEO transition recorded among emerging economy, nonetheless, the issue has not been well addressed in the literature. Disclosure policy in Malaysia also views change of CEO as an important element that will have an impact ont he firm value. To evaluate the CEO succession policy, this study investigates the effect of CEO transition announcement on the share price. This study adopts the event study method and employs two estimation models for expected return, which are Market Model (MM) and Capital Asset Pricing Model (CAPM).This study examines the simultaneous announcement, which indicates the adoption of succession policy, as well as the announcement of CEO appointment and CEO turnover. A total of354 announcements of CEO transition from 170 firms listed on Bursa Malaysia, over the duration of ten years from 2007-2016is observed. The result indicates that the firm’s share price generally reacts towards all types of CEO transition announcement, with a stronger reaction significantly observed through the simultaneous announcement. Further robustness check with regression analysis confirms that when the CEO transition announcement is simultaneous, it creates more value to the firm. In other words, the CEO succession policy, where proper CEO transition takes place, eliminates the uncertainty and risk, hence, giving a positive impact on firm value. This finding also contributes to the signalling theory literature, where anticipated event induces a positive reaction from investors, as reflected in the firm share price.